Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/bjd.16838
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and combination topical photodynamic therapy for basal cell carcinoma: systematic review and meta-analysis

Abstract: PDT is an effective treatment for low-risk BCC, with excellent cosmesis and safety. Imiquimod has higher efficacy than single-cycle PDT but more adverse effects. Highest efficacy is with excisional surgery. Fractionated and combination PDT options warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 50 publications
(106 reference statements)
2
56
0
6
Order By: Relevance
“…Imiquimod has higher efficacy than single-cycle PDT but more adverse effects, with surgery offering the highest efficacy. 151 This is in accordance with a further review and metanalysis of sBCC treatment options, where pooled estimates from randomized and nonrandomized studies showed similar tumour-free survival at 1 year for imiquimod and PDT, with highest success in studies with repeated treatments. 152 PDT is recommended as a good therapy for primary sBCC, fair for primary low-risk nBCC and the treatment of choice for large low-risk primary sBCC.…”
Section: Basal Cell Carcinomasupporting
confidence: 88%
See 1 more Smart Citation
“…Imiquimod has higher efficacy than single-cycle PDT but more adverse effects, with surgery offering the highest efficacy. 151 This is in accordance with a further review and metanalysis of sBCC treatment options, where pooled estimates from randomized and nonrandomized studies showed similar tumour-free survival at 1 year for imiquimod and PDT, with highest success in studies with repeated treatments. 152 PDT is recommended as a good therapy for primary sBCC, fair for primary low-risk nBCC and the treatment of choice for large low-risk primary sBCC.…”
Section: Basal Cell Carcinomasupporting
confidence: 88%
“…A systematic review and metanalysis concluded that PDT is effective for low‐risk BCC, with excellent cosmesis and safety. Imiquimod has higher efficacy than single‐cycle PDT but more adverse effects, with surgery offering the highest efficacy . This is in accordance with a further review and metanalysis of sBCC treatment options, where pooled estimates from randomized and nonrandomized studies showed similar tumour‐free survival at 1 year for imiquimod and PDT, with highest success in studies with repeated treatments .…”
Section: Basal Cell Carcinomasupporting
confidence: 86%
“…The recommendations are based on evidence drawn from systematic reviews of the literature pertaining to the clinical questions identified. The summary of findings with forest plots (Appendix B), GRADE evidence profiles indicating the quality of evidence (Appendix E), tables Linking the Evidence To the Recommendations (Appendix D), PRISMA flow diagram (Appendix I) and list of excluded studies (Appendix J) are detailed in the Supporting Information and a separate systematic review for basal cell carcinoma (BCC) . The strength of recommendation is expressed by the wording and symbols shown in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Topical PDT is listed as a treatment modality for superficial basal cell carcinoma (BCC) and thin nodular BCC in publish guidelines . In this issue of the BJD , Collier et al . present a rigorous, comprehensive systematic review and meta‐analysis of the use of PDT for BCC, the largest such analysis to date .…”
Section: Comparison Between Photodynamic Therapy (Pdt) and Surgery Fomentioning
confidence: 99%
“…In this issue of the BJD , Collier et al . present a rigorous, comprehensive systematic review and meta‐analysis of the use of PDT for BCC, the largest such analysis to date . Databases were searched until 1 September 2017; 15 randomized controlled trials were analysed that included over 2300 patients and over 3500 BCCs.…”
Section: Comparison Between Photodynamic Therapy (Pdt) and Surgery Fomentioning
confidence: 99%